Harriet Tubman (American experience, ,, 1961)
Description Not Provided

League of the Iroquois (American experience, AE12,, 1962)
Description Not Provided

A journal of the Pilgrims at Plymouth: Mourt's relation, a relation or journal of the English plantation settled at Plymouth in New England, by certain English adventurers both merchants and others (American experience, ,, 1963)
Description Not Provided

The Battle of Monmouth (New Jersey's revolutionary experience, 25,, 1964)
Traces the events of the Revolutionary War battle at Monmouth during which it is believed Mollie Pitcher aided the soldiers.

The Italians of Newark, a community study (Italian American experience, ,, 1975)
Description Not Provided

The vineyard of liberty (American experiment, ,, 1982)
Description Not Provided

The workshop of democracy (American experiment, ,, 1985)
Description Not Provided

From equal suffrage to equal rights: Alice Paul and the National Woman's Party, 1912-1928 (American social experience, 5,, 1986)
Description Not Provided

The crosswinds of freedom (American experiment, 3,, 1989)
Description Not Provided

Army of Manifest Destiny: the American soldier in the Mexican War, 1846-1848 (American social experience, 23,, 1992)
Description Not Provided

The Dutch-American farm (American social experience, 24,, 1992)
Description Not Provided

Between two fires: Black soldiers in the Civil War (African-American experience, ,, 1993)
Documents the recruitment, training, and struggles of African American soldiers during the Civil War and examines the campaigns in which they participated.

Historic speeches of African Americans (African-American experience, ,, 1993)
Presents speeches by various African American religious and political leaders from the days of slavery to the present, along with biographical information and historical background.

In the heart of Filipino America: immigrants from the Pacific isles (Asian American experience, ,, 1994)
Description Not Provided

Issei and nisei: the settling of Japanese America (Asian American experience, ,, 1994)
Description Not Provided

Journey to Gold Mountain: the Chinese in nineteenth-century America (Asian American experience, ,, 1994)
Description Not Provided

Spacious dreams: the first wave of Asian immigration (Asian American experience, ,, 1994)
A history of the first wave of Asian immigration in America.

"All my trials, Lord": selections from women's slave narratives (African-American experience, ,, 1995)
Description Not Provided

America goes to war: a social history of the Continental Army (American social experience, 33,, 1996)
A unique and revealing analysis of the diverse body that made up the American revolutionary army One of the images Americans hold most dear is that of the drum-beating, fire-eating Yankee Doodle Dandy rebel, overpowering his British adversaries through sheer grit and determination. The myth of the classless, independence-minded farmer or hard-working artisan-turned-soldier is deeply ingrained in the national psyche. Charles Neimeyer here separates fact from fiction, revealing for the first time who really served in the army during the Revolution and why. His conclusions are startling. Because the army relied primarily on those not connected to the new American aristocracy, the African Americans, Irish, Germans, Native Americans, laborers-for-hire, and "free white men on the move" who served in the army were only rarely altruistic patriots driven by a vision of liberty and national unity. Bringing to light the true composition of the enlisted ranks, the relationships of African-Americans and of Native Americans to the army, and numerous acts of mutiny, desertion, and resistance against officers and government, Charles Patrick Neimeyer here provides the first comprehensive and historically accurate portrait of the Continental soldier.

India in the West: South Asians in America (Asian American experience, ,, 1995)
Description Not Provided